PENGARUH PEMBERIAN JUS MENTIMUN TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS RANOTANA WERU KOTA MANADO - Ajiria, Zenab (Journal Of Community & Emergency, 2024)
Hypertension is a degenerative disease. Generally, blood pressure increases slowly with age. The risk for suffering from hypertension in the population over 55 years who had prehypertension blood pressure before they were diagnosed with hypertension occurred between the third and fifth decades of life. Until the age of 55 years, more men suffer from hypertension than women. From the age of 55 to 74 years, slightly more women than men suffer from hypertension. In the elderly population (over 60 years of age), the prevalence for hypertension is 65.4%. The aim of the study was to determine the effect of giving cucumber juice on reducing blood pressure in hypertension sufferers in the Ranotana Weru Health Center Work Area, Manado City. This type of research is an experimental study with a one group pre test post test design, which measures blood pressure before and after the case group treatment in November 2021 and the research site is at the Ranotana Weru Health Center. The statistical test used is the "Wilcoxon" statistical test with a 95% confidence degree if . The results showed that the value of P value = 0.001 while the value of = 0.05 Thus Ho is rejected and H1 is accepted, then there is an effect of giving cucumbers on reducing blood pressure in the community in the Work Area of ​​the Ranotana Weru Health Center, Manado City. Conclusion From the results of the study, blood pressure before consuming cucumber juice in patients with hypertension in the Work Area of ​​the Ranotana Weru Health Center, Manado City, most of the hypertension sufferers were at stage 2 and Stage 1. Blood pressure after consuming cucumber juice in patients with hypertension in the Work Area of ​​the Ranotana Weru Health Center Manado City Most people with hypertension are at normal blood pressure and prehypertension blood pressure. The suggestion in this research is that this research is expected to be input and add to the literature for educational institutions, especially about the effect of cucumber juice on high blood pressure or hypertension.